2017
DOI: 10.1007/s00268-017-4444-2
|View full text |Cite
|
Sign up to set email alerts
|

One‐Hour Postoperative Parathyroid Hormone Levels Do Not Reliably Predict Hypocalcemia After Thyroidectomy

Abstract: Following total thyroidectomy, PTH levels are unreliable in predicting hypocalcemia. Additional prospective studies are needed to understand the true utility of PTH levels post-thyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
0
12
0
7
Order By: Relevance
“…Although clinically convenient, such cutoffs and recommendations have limitations, as demonstrated by prior reports. [7][8][9][10] Although PTH level alone has quite good predictive ability in our cohort (AUC 4 0.79), our findings have also shown some limitations of this approach: PTH level cutoff in low normal range (19 pg/ mL, about 30% above lower limit of normal) would result in a false-negative rate <5 per cent. However, about 64 per cent of patients with PTH level below this threshold would not develop significant hypocalcemia.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although clinically convenient, such cutoffs and recommendations have limitations, as demonstrated by prior reports. [7][8][9][10] Although PTH level alone has quite good predictive ability in our cohort (AUC 4 0.79), our findings have also shown some limitations of this approach: PTH level cutoff in low normal range (19 pg/ mL, about 30% above lower limit of normal) would result in a false-negative rate <5 per cent. However, about 64 per cent of patients with PTH level below this threshold would not develop significant hypocalcemia.…”
Section: Discussionmentioning
confidence: 92%
“…Postoperative parathyroid hormone (PTH) levels were popularized as a means of identifying patients who may require prolonged observation. 4,5 However, several recent studies, [6][7][8][9][10] including a systematic review of 69 studies by Mathur et al, 11 have questioned the predictive value, and the sensitivity of PTH levels for detection of patients at risks for postoperative hypocalcemia. This systematic review found that although most studies reported PTH levels as predictive of symptomatic hypocalcemia, these studies evaluated fewer than 100 patients with postoperative hypocalcemia and were inconsistent with regards to methodology.…”
mentioning
confidence: 99%
“…Numerosos estudios han utilizado la PTH como predictor de hipocalcemia postiroidectomía, demostrando valores adecuados de sensibilidad, especificidad y valores predictivos negativo y positivo, con una ligera superioridad con respecto al monitoreo del calcio 7,8,10,13 . Si bien los estudios son muy heterogéneos en cuanto a variables y formas de medición, la sensibilidad propuesta varía del 69 al 100% en una muestra tomada entre la primera y las 24 horas del posoperatorio 7,8,15 .…”
Section: Eficacia De La Pth Como Predictorunclassified
“…Por su parte, Hermann, et al 20 determinaron que unos valores de PTH iguales o por debajo de 6 pg/ml tendrían una sensibilidad del 100% y un valor predictivo positivo del 15% para el hipoparatiroidismo definitivo 20 . Sin embargo, otros estudios, como el de Sahli, et al 15 , descartan dicha correspondencia. Su trabajo, con 218 pacientes incluidos, descartó la PTH medida dentro de la primera hora poscirugía como predictor confiable de hipocalcemia, alegando su baja sensibilidad (36,5%); entre sus conclusiones, destaca la necesidad de estudios aleatorizados para llegar a una conclusión más acertada.…”
Section: Eficacia De La Pth Como Predictorunclassified
“…Regarding the validity of the study assumptions we are concerned about the lack of a strict protocol on the timing of post-surgical iPTH sampling; almost one-third of the patients were tested in the first 2 h, 11.8% between 2 and 3 h post thyroidectomy, and only the remaining 61.4% (n = 62) were sampled for measurement of iPTH at 4 h. Various studies [2,3] have examined the utility of measuring intraoperative or postoperative intact PTH levels drawn at various time points in the post-thyroidectomy period, and the timing of PTH measurements in published studies has ranged from 10 min to 24 h post-thyroidectomy. Still, there is a significant variation in thresholds to predict hypocalcemia in the published literature.…”
Section: To the Editormentioning
confidence: 99%